Individualization of physical loads and speed abilities of young soccer players in a six-month training macrocycle - Andrzejewski, M.; Chmura, J.; Strzelczyk, R.; Konarski, J. (Journal of Human Kinetics, 2009)
The aim of this paper was to address the issue of individualized training loads and its influence on speed development among speed-type and endurance-type players during a six-month training macrocycle. The research was conducted in a group of 36 young male soccer players from for two sport clubs: Lech Poznan and Warta Poznan. The stages of the study undertaken resulted from the time structure of sport training and were carried out during a six-month macrocycle. The players of Lech Poznan took part in a test which involved applying three series` (six repetitions each) of speed-type exercises, with regard to the player's motor type in each of the three training units comprising the weekly macrocycle. During each stage of data collection, the players were subjected to a stress test for stretches of 10, 20 and 30 m. The study has shown a significant impact of individualization of training loads on development of speed abilities in the examined players. An increase of speed during the tests of 10 and 20 m was noted in both speed and endurance-type players. This was probably an effect of adapting individual training loads to motor predispositions of the players during the six months of the experiment. It can be also assumed that the increase in speed among the subjects is a result of rising phosphagen potential and enzymatic activity (especially creatine kinase), as well as improved motor units recruitment.